Integração entre normas de gestão da qualidade em uma empresa fornecedora da cadeia nuclear - Campos, Renato Augusto (Universidade Federal de São Carlos, 2019)
Nuclear supplier organizations, due to regulatory requirements, pioneered the implementation of quality assurance programs in Brazil. CNEN NN 1.16 is a national standardization standard aimed at determining the requirements in the establishment and implementation of quality assurance systems in nuclear installations. On the other hand, ISO 9001: 2015 is the main ISO 9000 family standard, has quality management system requirements and aims for certification. In June 2018, ISO 19443 was published, which applies the principles of ISO 9001, combining best quality practices with specific requirements of the nuclear industry. Considering the advantages of integrating management systems, this research aims to analyze the benefits and difficulties in integrating CNEN-NN-1.16 and ISO 9001:15 standards in a nuclear chain supplier company. It is also a research objective to analyze which benefits that ISO 19443 can bring to this integrated system. The research, exploratory and qualitative in nature, used as a method of procedure the case study. Data collection was done through interviews, document analysis and participant observation. Among the results, it is noted that CNEN-NN-1.16 was published in 1999 and underwent a review in 2000, so the research demonstrates that a new revision is necessary, based on the requirements of NBR ISO 9001: 2015 and ISO 19443, such as: risk management, stakeholder management, organizational context. By critically analyzing these requirements, their potential contribution to CNEN-NN-1.16 is believed. In the organization studied, it was found that the integrated use of standards can bring benefits, however, during the implementation of NBR ISO 9001:15 and CNEN-NN-1.16, problems related to lack of training, level of worker commitment were noticed and resistance to change. These problems diminished and tended to die out as the system matured.
Integration between quality management standards in a nuclear supplier company
Keywords: Sistemas integrados de gestão; NBR ISO 9001; CNEN NN 1.16; ISO 19443; Nuclear; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO